Enhancing plant growth promoting rhizobacterial activities through consortium exposure: A review - Singh, Anamika; Yadav, Virendra Kumar; Chundawat, Rajendra Singh; Soltane, Raya; Awwad, Nasser S.; Ibrahium, Hala A.; Yadav, Krishna Kumar; Vicas, Simona Ioana (Frontiers in Bioengineering and Biotechnology, 2023)
Plant Growth Promoting Rhizobacteria (PGPR) has gained immense importance in the last decade due to its in-depth study and role of the rhizosphere as an ecological unit in the biosphere. A putative PGPR is considered PGPR only when it may have a positive impact on the plant after inoculation. From the various pieces of literature, it has been found thatthese bacteria improve the growth of plants and their products through their plant growth-promoting activities. A microbial consortium has a positive effect on the plant growth promoting (PGP) activities evident from the literature. In the natural ecosystem, rhizobacteria interact synergistically and antagonistically with each other in the form of a consortium, but in a natural consortium, there are various oscillating environmental conditions that affect the potential mechanism of consortium. For the sustainable development of our ecological environment, it is our utmost necessity to maintain the stability of the rhizobacterial consortium in fluctuating environmental conditions and for those various studies has been conducted to design synthetic rhizobacterial consortium in the last decade. In this review, the authors have emphasized to cover all the studies on designing synthetic rhizobacterial consortiums, their strategies, mechanism, and their application in the field of environmental ecology and biotechnology.